2022
DOI: 10.1038/s41562-021-01247-w
|View full text |Cite|
|
Sign up to set email alerts
|

Subjective confidence reflects representation of Bayesian probability in cortex

Abstract: What gives rise to the human sense of confidence? Here, we tested the Bayesian hypothesis that confidence is based on a probability distribution represented in neural population activity. We implemented several computational models of confidence, and tested their predictions using psychophysics and fMRI. Using a generative model-based fMRI decoding approach, we extracted probability distributions from neural population activity in human visual cortex. We found that subjective confidence tracks the shape of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 82 publications
12
84
1
Order By: Relevance
“…Similar results are observed for a single remembered location (Li et al, 2021), a single cued location among multiple items (Yoo et al, 2018), and a single cued color among multiple items (Honig et al, 2020). Moreover, a pair of recent fMRI studies have established a link between the quality of decoded neural representations from areas of visual and parietal cortex and reports of memory uncertainty for spatial location (Li et al, 2021) and grating orientation (Geurts et al, 2022). Both of these studies observed a trial-by-trial correlation between a model-based measure of uncertainty of the decoded neural representation and a behavioral report of memory uncertainty, supporting a model whereby observers are directly reading out the quality of their neural representations when making an evaluative judgment of a single WM representation.…”
Section: Evaluating the Quality Of Wm Representationssupporting
confidence: 71%
See 2 more Smart Citations
“…Similar results are observed for a single remembered location (Li et al, 2021), a single cued location among multiple items (Yoo et al, 2018), and a single cued color among multiple items (Honig et al, 2020). Moreover, a pair of recent fMRI studies have established a link between the quality of decoded neural representations from areas of visual and parietal cortex and reports of memory uncertainty for spatial location (Li et al, 2021) and grating orientation (Geurts et al, 2022). Both of these studies observed a trial-by-trial correlation between a model-based measure of uncertainty of the decoded neural representation and a behavioral report of memory uncertainty, supporting a model whereby observers are directly reading out the quality of their neural representations when making an evaluative judgment of a single WM representation.…”
Section: Evaluating the Quality Of Wm Representationssupporting
confidence: 71%
“…For example, the activity pattern across a population of neurons in primary visual cortex accurately encodes the orientation of an oriented grating which can be decoded using a variety of machine learning methods (Berens et al, 2012;Stringer et al, 2021;Walker et al, 2020). Theoretical (Ma et al, 2006) and empirical (Geurts et al, 2022;Li et al, 2021;van Bergen et al, 2015;Walker et al, 2020) studies have supported the notion that neural population codes additionally (and implicitly) encode the 'quality' or 'uncertainty' of a representation. Rather than separately keeping track of the feature value represented by a neural population and its uncertainty, both of these types of information are simultaneously encoded in a probability distribution carried by the neural activity pattern.…”
Section: Implications For Neural Population Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the aINS generates higher-order interoceptive predictions and interoceptive prediction errors by computing the difference between its predictions and forward signals arriving from the dINS. Evidence that the insula is involved in computation of predictions or more specifically in generation of interoceptive predictions and uses Bayesian belief updating is still scarce, but has started to emerge from human and animal experiments [134][135][136][137][138][139][140][141][142][143].…”
Section: Insula Hierarchical Modular Adaptive Interoception Controlmentioning
confidence: 99%
“…The same also applies to moving stimuli in the MT cortex 3 and neural firing in response to visual stimuli in general resembles probability density functions 4 . Decoding of these neural activities, both in visual and prefrontal cortices, demonstrate correlations with reported confidence 5 , suggesting that people are aware of and can report their internal representations at least to some extent. Given that neural representations are probabilistic, how could perception be discrete?…”
Section: Introductionmentioning
confidence: 97%